Metabolic outcomes of laparoscopic sleeve gastrectomy. Issue 1 (January 2018) - Kaisar, Hany H.; Shafik, Youhanna S.
Abstract : Background: Laparoscopic sleeve gastrectomy (LSG) is a recently developed technique for treating morbid obesity. As it is a simple procedure, many bariatric surgeons have adopted it in recent years with good results. LSG is a purely gastric restrictive procedure designed to reduce appetite by decreasing the size of the stomach. Objectives: The aim of this study was to investigate the metabolic outcomes of LSG, including rate of weight loss, amelioration of obesity-related comorbidities as well as the intraoperative and postoperative complications. Patients and methods: From August 2011 to August 2013, 60 consecutive patients with morbid obesity (eight males and 52 females) underwent laparoscopic sleeve gastrectomy at the Ain Shams University Hospital (El-Demerdash) and Ain Shams Specialized Hospital. Follow-up of the patients was done for a period of 2 years to investigate the preliminary results of this procedure including operative morbidity and mortality, short-term and long-term complications, rates and parameters of weight loss, as well as the effect on lipid and energy metabolism. Results: There were two cases [2/60 (3.3%)] with intra-abdominal bleeding following LSG. Staple-line failure was detected in two cases [2/60 (3.3%)], two early complications [2/60 (3.3%)] were encountered, and late complications occurred in two patients [2/30 (3.3%)], with no mortality occurred. Substantial weight loss occurred in all patients. Mean excess weight loss was 48.04±4.34% at the end of first year and 67.85±3.75% at the end of the second year. Complete resolution of comorbidities was 73.3% for hypertension and 80% for diabetes mellitus at the end of second year. Conclusion: LSG is a feasible and safe restrictive bariatric procedure, with good short-term results. It offers the advantages of a simple and reproducible technique with good outcome and low morbidity and mortality. LSG is accepted as a standalone definitive therapy, as it has a high percentage of postoperative excess weight loss as well as reduction of obesity-related comorbidities.